Romance of Transportation Parade, 1936. - Jones, Frank (Forsyth County Public Library)
TCS 12/30/36.
Romance of Transportation Parade, 1936. Photograph shows men riding on an early fire truck.
Keywords: Winston-Salem (N.C.); Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth